Vulnerabilidade em saúde de gestantes à transmissão vertical da sífilis no contexto da Atenção Primária à Saúde: construção e validação de itens - Sousa, Ana Jessyca Campos (2022)
The objective was to construct and validate Items corresponding to the health vulnerabilities of pregnant women to vertical transmission of syphilis to be applied in Primary Health Care. This is a methodological study with a quantitative and qualitative approach. The first stage of the research was the elaboration of a Scope Review based on the guiding question “What are the Operational Definitions of vulnerability of pregnant women to the transmission of congenital syphilis in PHC, evidenced in the health sciences literature?”. The search for studies took place in the following databases: Scientific and Technical Literature of Latin America and the Caribbean (LILACS); Medical Literature Analysis and Retrieval System Online (MEDLINE), EMBASE, CINAHL and Scopus Preview (SCOPUS). After reading and critically analyzing the selected studies, the OD of the health vulnerabilities of pregnant women in the context of SC was identified, based on what was proposed by Florêncio (2018). Then, the DO Items were built and validated. For this, Content Validation was adopted, carried out by eight specialists on the subject through Google forms. The content of the responses was monitored in real time on the website and compiled into Microsoft Excel spreadsheets. Their answers were descriptively evaluated and discussed according to the relevant literature. After the evaluation of the judges, the adaptations suggested by them were carried out. For quantitative analysis, the CVI was used with an acceptable minimum of 0.75. To verify the proportion of judges who considered the item adequate, the Binomial Test was used, defining a value equal to or greater than 80% to consider the item adequate if the test did not present statistical significance (p > 0.05). To measure the homogeneity of the measures, the Intraclass Correlation Coefficient was used, obtaining a result of 0.73, classifying it as substantial. The items were considered validated in terms of their content, with a CVI ranging from 0.87 to 1.0 and a binomial test of 13.0, showing the satisfaction of the judges with the material. The Intraclass Correlation Coefficient was 0.73, considered substantial possibly due to the different experiences as well as the different regions of residence of the judges